Dosimetric Verification Using Optically Stimulated Luminescence (Osld) Nanodots For Postero-Anterior (Pa) Chest Examinations In Perak Health Clinics - Saidin, Mohd Tarmizi (2021)
The study was conducted to determine the patients dosimetry received in carrying out an X-ray Examination Procedure at the Perak Health Clinic. As a result of this study the Entrance Surface Dose (ESD) measurement of the procedure will be recorded. There are a number of diagnostic procedures implemented at the Health Clinic where most of the cases are for Postero – Anterior (PA) Chest imaging procedures. Therefore, dosimetry measurements for PA Chest imaging procedures will be recorded for the exposure factors used by the radiographer at the Health Clinic. The measurement of the dosimetry ESD will use the Nanodots OSLD (Al2 O3: C) placed on the Perspex phantom with a thickness of 10 cm and recorded in the unit of mGy. Dosimetry ESD units measured using Nanodots OSLD for the PA Chest imaging procedure for the Perak Health Clinic were recorded and reported as mean, median, first and third quartile values. Basically the recorded ESD measurements are found to be lower than the guideline level set for PA Chest X-ray examination in Malaysia as a guide for the Dose Reference Level (DRL) recommended by the Ministry of Health Malaysia is 0.9 mGy and also by the International Atomic Agency (IAEA) is 0.4 mGy. In addtion, research study results is able to determine the ESD value from all clinics will include machines at Health Clinics in Perak based on models such as Shimadzu, Philip, Toshiba, Siemens GE and Bennett Hologic. Measurements using Nanodots OSLD will provide the maximum reading and minimum ESD for each involved clinics.